Study Of Basic Concept Formulation In The Design Of Pandalungan Cultural Gallery In The Coastal Area Of Jember Regency - Ihza Maulana Zaen; Retno Hastijanti; Khoudiy Iffiyah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Pandalungan culture represents the cultural identity of the Jember community, which emerged from the interaction and blending of Javanese and Madurese traditions. This cultural combination shapes unique social patterns, artistic expressions, and cultural systems within society. Despite its rich cultural diversity, Jember still lacks an integrated facility that can accommodate activities related to cultural education, preservation, and appreciation. This condition is particularly evident in coastal areas, which function as public spaces and important tourism corridors. In response to this issue, the gallery design adopts the concept of “Lahbako Pesisiran,” an approach that combines the communal values reflected in the Lahbako tradition with the open and adaptive character of coastal environments. The design process involves analyzing users, activities, and site context to develop spatial strategies that emphasize learning, social interaction, and creativity. The study shows that integrating local cultural values with coastal environmental potential can create a cultural facility that supports preservation while strengthening public space and cultural identity.